Artificial intelligence and law: Regulatory challenges, liability, and human rights in the digital age - Maizi, Allel (The International tax journal, 2026)
This article examines the legal challenges that artificial intelligence poses to modern legal systems through a three-dimensional analytical approach encompassing (i) the legal and regulatory framework, (ii) legal liability, and (iii) ethical considerations and human rights. The study highlights that traditional legislation is no longer capable of adequately accommodating the novel legal realities generated by intelligent systems, particularly those associated with relatively autonomous automated decision-making. The article further discusses the difficulties of attributing civil and criminal liability for harm caused by artificial intelligence, as well as the risks posed by algorithmic bias and a lack of transparency. It concludes by underscoring the need to adopt an integrated and adaptable legal framework that strikes an appropriate balance between fostering innovation and safeguarding fundamental rights and freedoms.